In Vitro Evaluation of Fusiform-Shaped Stents for Wide-Neck Intracranial Aneurysm Treatment - Jia, Zhen Yu (Neurointervention, 2018)
PURPOSE: Wide-neck aneurysms (WNAs) associated with a dilated parent artery (PA) are not uncommon morphological abnormalities and usually cause inappropriate wall apposition and incomplete neck coverage of a tubular stent in stent-assisted coiling of aneurysms. We aimed to introduce a fusiform-shaped stent (FSS) and test its effectiveness in treating intracranial WNAs associated with a dilated PA using a three-dimensional (3D) model. MATERIALS AND METHODS: Two FSS types were designed with the middle one-third segment dilated by 10% (FSS10) and 20% (FSS20) and were compared with the tubular-shaped stent (TSS). A patient-specific 3D WNA model was prototyped and produced, and in vitro stent placement was performed. Angiographic images of the three stent types were analyzed and compared using predetermined parameters. RESULTS: The stent lumens were significantly larger in FSS10 and FSS20 than in TSS in the middle segments (P=0.046), particularly FSS20 (P=0.018). The non-covered area at the ostium tended to be smaller in FSS10 and FSS20 than in TSS, but the difference was not significant (P>0.05). The stent length was significantly longer in FSS10 and FSS20 than in TSS. The stent cell size was significantly larger in FSS than in TSS. CONCLUSION: Better vessel wall apposition and aneurysmal neck coverage was observed for FSS than for TSS. No significant difference was observed between FSS10 and FSS20.